THE LONG-TERM EVOLUTION OF IMMUNE DEPOSITS IN PASSIVE HEYMANN NEPHRITIS - Soares, V. A.; Almeida, D. B. (Associação Brasileira de Divulgação Científica (ABRADIC), 1992)
1. To study the long term course of passive Heymann nephritis (PHN), 42 adult male Wistar rats were injected with rabbit anti-FX1A serum (PHN group) and 42 rats received normal rabbit serum (control group). Two animals from each group were sacrificed 2 weeks after the inoculation and 10 animals each from the control and PHN groups were sacrificed 4, 13, 25 and 53 weeks later.2. The PHN group exhibited a significant elevation in 20-h proteinuria which lasted from the first week (control group, 9.19 +/- 0.87; PHN group, 25.3 +/- 2.66) to the 25th week (control group, 22.6 +/- 2.15; PHN group, 66.7 +/- 10.4) except for week 17. From week 29 to week 53 there was no statistical difference between the 2 groups.3. Light microscopy showed no difference between the kidneys of PHN and control rats. Immunofluorescence microscopy in PHN rats showed granular deposition of autologous and heterologous IgG on the glomerular basement membrane (GBM), whose intensity and pattern did not change during 53 weeks of observation.4. When examined by electron microscopy the glomeruli of PHN rats showed: a) electron-dense deposits which were initially subepithelial and homogeneous and later intramembranous, granular and often surrounded by an electron-transparent halo; b) focal thickening of the GBM at the sites of intramembranous deposits; c) effacement of podocytes located close to the deposits; d) penetration of the podocytes into the GBM associated with the deposits; e) presence of osmiophilic granules in the cytoplasm of the podocyte located inside the GBM similar to the granules of the deposits next to them. The association of the penetration of the podocytes into the GBM with the deposits and the presence of the osmiophilic granules inside the foot process have not been described previously in PHN.5. The results suggest that the podocytes play a role in the clearing of intramembranous deposits in PHN.
Keywords: IMMUNE DEPOSITS; PASSIVE HEYMANN NEPHRITIS; PODOCYTES; PROTEINURIA; GLOMERULAR BASEMENT MEMBRANE